PERBANDINGAN PENERAPAN METODE DRILL DAN RESITASI TERHADAP HASIL BELAJAR KOGNITIF MATEMATIKA SISWA KELAS XI IPA DI SMA ABC CIKARANG [A COMPARISON OF THE IMPLEMENTATION OF DRILL AND RECITATION METHODS TOWARD GRADE 11 SCIENCE STUDENTS’ COGNITIVE ACHIEVEMENT AT A HIGH SCHOOL IN CIKARANG] - Soponyono, Andreas Eko; Sinaga, Kelly; Seleky, Jacob S. (Universitas Pelita Harapan, 2018)
This research aims to investigate the comparison of the improvement average in student’s mathematics cognitive learning outcomes between an 11th grade science class taught by drill strategy and by recitation method. This research used quasi-experimental with pre-test post-test comparison group design. The sample was taken by a convenient random sampling. The instruments were tried before being given to the research sample to measure the validity, reliability, difficulty index and discriminating power. The analysis uses the U Mann-Whitney test. The results of the research show that there are no different improvement average in mathematics cognitive outcomes between an 11th grade science class that taught by drill and by recitation method (p= 0,152 > 0,05).BAHASA INDONESIA ABSTRAK: Tujuan penelitian ini untuk menyelidiki perbandingan peningkatan hasil belajar kognitif Matematika antara siswa kelas XI IPA yang mengalami pembelajaran dengan metode drill dan yang dengan resitasi. Metode penelitian yang digunakan adalah kuasi eksperimen dengan pre-test post-test comparison group design. Instrumen telah diujicoba sebelum diberikan kepada sampel penelitian untuk mengukur validitas, reliabilitas, taraf kesukaran dan daya pembeda. Analisis data menggunakan tes U Mann-Whitney. Hasil penelitian menunjukkan bahwa tidak terdapat perbedaan peningkatan hasil belajar kognitif Matematika antara siswa yang diterapkan metode drill dengan yang diterapkan metode resitasi (p= 0,152 > 0,05).